Rāmaśāhako jīvana caritra : yauṭā purānū vaṃśāvalīkā ādhāramā - Jñavāli, Sūryavikrama (SAMP early 20th-century Indian books project, 1933)
Biography of Ram Shah, one of the early Shah rulars of Gorkha.